Experiences and perceptions of care-seeking for febrile illness among caregivers, pregnant women, and health providers in eight districts of Madagascar - Rachel Favero; Catherine M. Dentinger; Jean Pierre Rakotovao; Laurent Kapesa; Haja Andriamiharisoa; Laura C. Steinhardt; Bakoly Randrianarisoa; Reena Sethi; Patricia Gomez; Jocelyn Razafindrakoto; Eliane Razafimandimby; Ralaivaomisa Andrianandraina; et al. (Malaria Journal, 2022)
Abstract Background Prompt diagnosis and treatment of malaria contributes to reduced morbidity, particularly among children and pregnant women; however, in Madagascar, care-seeking for febrile illness is often delayed. To describe factors influencing decisions for prompt care-seeking among caregivers of children aged < 15 years and pregnant women, a mixed-methods assessment was conducted with providers (HP), community health volunteers (CHV) and community members. Methods One health district from each of eight malaria-endemic zones of Madagascar were purposefully selected based on reported higher malaria transmission. Within districts, one urban and one rural community were randomly selected for participation. In-depth interviews (IDI) and focus group discussions (FGD) were conducted with caregivers, pregnant women, CHVs and HPs in these 16 communities to describe practices and, for HPs, system characteristics that support or inhibit care-seeking. Knowledge tests on malaria case management guidelines were administered to HPs, and logistics management systems were reviewed. Results Participants from eight rural and eight urban communities included 31 HPs from 10 public and 8 private Health Facilities (HF), five CHVs, 102 caregivers and 90 pregnant women. All participants in FGDs and IDIs reported that care-seeking for fever is frequently delayed until the ill person does not respond to home treatment or symptoms become more severe. Key care-seeking determinants for caregivers and pregnant women included cost, travel time and distance, and perception that the quality of care in HFs was poor. HPs felt that lack of commodities and heavy workloads hindered their ability to provide quality malaria care services. Malaria commodities were generally more available in public versus private HFs. CHVs were generally not consulted for malaria care and had limited commodities. Conclusions Reducing cost and travel time to care and improving the quality of care may increase prompt care-seeking among vulnerable populations experiencing febrile illness. For patients, perceptions and quality of care could be improved with more reliable supplies, extended HF operating hours and staffing, supportive demeanors of HPs and seeking care with CHVs. For providers, malaria services could be improved by increasing the reliability of supply chains and providing additional staffing. CHVs may be an under-utilized resource for sick children.